Insetos produtores de galhas como bioindicadores da recuperação de terras em uma área da Mata Atlântica Brasileira (Lundiana: International Journal of Biodiversity, 2008)
Galling insects may represent an excellent tool to evaluate habitat quality and restoration. We used galling insect species richness to evaluate the success of a project on reforestation in an Atlantic Forest area in southeastern Brazil. We selected 18 study sites from three distinct environments under succession: early stage (3-5 years old abandoned pasture), intermediate stage (10-15 years old), and intermediate stage sites under Myracrodruon urundeuva trees (10-15 years old). The highest galling species richness was found in the intermediate stage sites, followed by areas of early stages, while intermediate sites under M. urundeuva trees supported the lowest richness. The significant difference between areas under M. urundeuva and the other two suggests that this plant negatively impacts the plant community. Personal observations suggest an allelopathic activity of M. urundeuva, decreasing native species establishment, consequently reducing associated herbivore richness. Our results indicate that galling species were efficient tools to evaluate environmental quality in a degraded area of Atlantic Forest.Keywords: bioindicators, degraded area, insect galls, restoration ecology.